(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article discusses an innovative method for obtaining refined solid fuel using a pyrolysis plant and the development of a technology for processing low-grade coals from the southern region of Kyrgyzstan. The purpose of the research is to develop a technology for obtaining refined fuel from low-grade coals in Kyrgyzstan and their effective use in the heat and power industry and the construction industry of the country. The novelty of the proposed idea is the use of a pyrolysis plant to obtain refined solid fuel and the development of a technology for processing low-grade coals; as a result of experimental studies, high-quality import-substitutable fuel was obtained - semi-coke.